Dissecting the role of NETosis-related biomarkers in Sepsis: An integrated multi-dataset analysis for diagnostic and prognostic applications - Binming Qiu; Xue Zhang; Huanlan Chen (PLoS ONE, 2025)
Sepsis is a life-threatening condition with high mortality and economic burdens. The study analyzed non-redundant differentially expressed genes (DEGs) to elucidate neutrophil extracellular trap (NET) formation’s role in sepsis pathogenesis using high-throughput microarray and bioinformatics. Our comprehensive analysis meticulously identified a total of 629 DEGs, encompassing 348 upregulated and 281 downregulated genes. Through further scrutiny, we discovered 37 NETosis-related differentially expressed genes (NRDEGs) that showcased distinct expression patterns. Enrichment analysis vividly revealed the significant involvement of these NRDEGs in pathways related to NET formation, phagocytosis, and lymphocyte migration, thereby highlighting the crucial role of neutrophils in the immune response during sepsis. Additionally, CIBERSORT algorithm analysis indicated substantial differences in the abundance of 17 immune cell types between the sepsis and control groups, further reinforcing the altered immune landscape in sepsis patients. A protein-protein interaction (PPI) network constructed from the NRDEGs identified nine core genes, suggesting their potential central position in the pathophysiology of sepsis. Receiver operating characteristic (ROC) curve analysis demonstrated that ITGAM , CXCR 2, and FCGR 3 B exhibited extremely high accuracy in distinguishing sepsis from controls (with an area under the curve greater than 0.9). These remarkable findings strongly underscore the potential of these genes as biomarkers for early diagnosis and therapeutic targets in sepsis, emphasizing the urgent need for further validation in clinical settings to enhance diagnostic accuracy and refine treatment strategies. Overall, this study provides novel insights into the molecular mechanisms underlying sepsis, paving the way for improved clinical interventions.